2008
DOI: 10.1002/chem.200801003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nature of the Metal Atom on Hydrogen Bonding and Proton Transfer to [Cp*MH3(dppe)]: Tungsten versus Molybdenum

Abstract: The hydrogen-bonding and proton-transfer pathway to complex [Cp*W(dppe)H(3)] (Cp*=eta(5)-C(5)Me(5); dppe=Ph(2)PCH(2)CH(2)PPh(2)) was investigated experimentally by IR, NMR, UV/Vis spectroscopy in the presence of fluorinated alcohols, p-nitrophenol, and HBF(4), and by using DFT calculations for the [CpW(dhpe)H(3)] model (Cp=eta(5)-C(5)H(5); dhpe=H(2)PCH(2)CH(2)PH(2)) and for the real system. A study of the interaction with weak acids (CH(2)FCH(2)OH, CF(3)CH(2)OH, (CF(3))(2)CHOH) allowed the determination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“…Also the crucial H1−H2 distance is slightly shorter in Cp i Pr 4 molecule than in Cp t Bu 3 (Table 1). Theoretical investigations of similar complexes 26,27 produced distances in agreement with our structures, and a molecular dynamic simulation study confirmed a high probability of trihydride structures for related Mo complexes. 28 Full sets of geometrical data for all compounds in GP, THF, and MeCN as well as superposition of the most stable calculated structures with the experimental ones are given in section S.II of the SI.…”
Section: ■ Computational Detailssupporting
confidence: 89%
“…Also the crucial H1−H2 distance is slightly shorter in Cp i Pr 4 molecule than in Cp t Bu 3 (Table 1). Theoretical investigations of similar complexes 26,27 produced distances in agreement with our structures, and a molecular dynamic simulation study confirmed a high probability of trihydride structures for related Mo complexes. 28 Full sets of geometrical data for all compounds in GP, THF, and MeCN as well as superposition of the most stable calculated structures with the experimental ones are given in section S.II of the SI.…”
Section: ■ Computational Detailssupporting
confidence: 89%
“…E j Cp 2 Ru (0.67) < Cp 2 Os (0.81) and Cp* 2 Ru (0.85) < Cp* 2 Os (1.05)]. [21,70,71] The orbital component of a classical hydrogen bond is of donor-acceptor nature; the lone pair orbital of the base donates electrons to an empty s à AH orbital that has its main coeffi- www.chemphyschem.org cient on the protonic hydrogen atom (Figure 9 a). Such increase of the M···H interaction strength for 5d transition metals seems to be a general trend.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Hydrogen bonds play a key role as initial stage of the proton-transfer reaction to organic bases. Participation of the metal atom in hydrogen bonding at a hydride site was shown to assist direct proton transfer to W and Os in the case of [Cp*WH 3 (dppe)] [21] (Cp* = h 5 -C 5 Me 5 ) and [Cp*OsH(dppe)] [22] (dppe = k 2 -Ph 2 PCH 2 CH 2 PPh 2 ). [7,17] Basic knowledge accumulated over the last two decades suggests that a direct proton transfer to a metal lone pair is an unlikely event in the presence of hydride ligands, which are considered to be the kinetic site of proton attack even if classical di(poly)hydride were the thermodynamic protonation product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron removal is accompanied by a drastic pKa decrease [24] and therefore the 17-electron species suffer deprotonation. The proton may be captured by the medium, namely a base, the solvent or traces of H 2 O, or by the neutral hydride that may itself be susceptible to protonation, leading to cationic dihydrogen or dihydride compounds [25][26][27][28]. Electrochemical studies of halfsandwich molybdenum and tungsten complexes have received considerable attention and it was reported that subsequently to deprotonation, the 17-electron radicals may be trapped by the solvent and further oxidised or dimerize through radical coupling [24,[29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%